Efeito de um quelante de cálcio, um detergente e da lecitina de soja sobre a qualidade do sêmen caprino congelado-descongelado - Bittencourt, Rodrigo Freitas [UNESP]; Ribeiro Filho, Antönio de Lisboa; Lima, Marcos Chalhoub Coelho; Alves, Sidney Gonc̈alves Gonzalez; Vasconcelos, Marta Freitas; Biscarde, Carmo Emanuel [UNESP]; Leal, Luciana da Silva [UNESP]; Oba, Eunice [UNESP] (My University, 2008)
The aim of this paper was verifying the effect of the Equex STM Paste and EDTA addition to a Tris-egg yolk extender, on the postthaw goat sperm viability. Nine semen samples of two adult goats were collected by artificial vagina and cryopreserved. It was also objective of this study, to evaluate the utilization of a soybean lecithin based commercial extender (Bioexcell® - IMV, L'Aigle, French) for the goat semen freezing. They were formed five experimental groups: TRIS; TRIS+EDTA; TRIS+EQUEX; TRIS+EDTA+EQUEX e Bioexcell. After evaluation, the semen was diluted in the five extenders and packed in 0.25mL straws with 100 million of motile spermatozoa. The samples were cooled at 0,46°C/min to 5°C, submitted at 75min of equilibration time and frozen in liquid nitrogen vapour. The thawing was accomplished in 37°C water bath for 50s. There were no differences (P>0,05) on the means of post-thaw total and progressive sperm motility among the groups TRIS, TRIS+EQUEX and TRIS+EQUEX+EDTA. The Bioexcell group obtained the least (P<0,05) percentage of post-thawing total and progressive sperm motility. After the thermotolerance test, it was observed the greatest (P<0,05) rates of total and progressive sperm motility in the Equex STM groups (TRIS+EQUEX and TRIS+EQUEX+EDTA). Thus, it can be affirmed that the Equex addition promotes better maintenance rates in the pos-thaw sperm viability, when compared with the extenders that did not contain it.
Effects of a calcium chelator, a detergent and the soybean lecithin on the quality of the frozen-thawed goat semen
Keywords: Cryopreservation; Extender; Goat; Semen; Capra hircus; Glycine max